Lacosamide cardiac safety: clinical trials in patients with partial‐onset seizures. (30th April 2015) - Rudd, G. D.; Haverkamp, W.; Mason, J. W.; Wenger, T.; Jay, G.; Hebert, D.; Doty, P.; Horstmann, R.
<x xml:space="preserve">Abstract</x> Objective To evaluate the cardiac safety of adjunctive lacosamide in a large pool of adults with partial‐onset seizures (POS). Methods Post‐randomization changes from baseline for electrocardiographic (ECG) measurements, diagnostic findings, and relevant adverse events (AEs) were compared for pooled data from three randomized, placebo‐controlled trials of adjunctive lacosamide for the treatment of POS. Results Lacosamide did not prolong the QTc interval or affect heart rate as determined by an analysis of data from patients randomized to lacosamide 200, 400, or 600 mg/day (n = 944) compared with placebo (n = 364). After 12‐week maintenance treatment, mean changes from baseline for QRS duration were similar between the placebo and lacosamide 200 and 400 mg/day groups (0.0, −0.2, and 0.4 ms), but slightly increased for lacosamide 600 mg/day (2.3 ms). A small, dose‐related mean increase in PR interval was observed (−0.3, 1.4, 4.4, and 6.6 ms for the placebo and lacosamide 200, 400, and 600 mg/day groups, respectively). First‐degree atrioventricular (AV) block was reported as a non‐serious AE in 0.0%, 0.7%, 0.2%, and 0.5% of patients in the same respective groups. Second‐ or higher degree AV block was not observed. There was no evidence of a PR‐interval‐related pharmacodynamic interaction of lacosamide with either carbamazepine or lamotrigine. Conclusions Evaluation of the pooled cardiac safety data from patients with POS showed that adjunctive lacosamide at the maximum recommended dose (400 mg/day) was not clearly associated with any cardiac effect other than a small, dose‐related increase in PR interval that had no evident symptomatic consequence.